Empirical rainfall thresholds for mudflow events in an arid basin of the Peruvian coast - Goyburo, Andres; Gutierrez, Leonardo; Rau, Pedro; Lavado-Casimiro, Waldo (Frontiers in Water, 2025)
Mudflows, a highly destructive natural phenomenon, frequently occurs in arid regions due to the activation of basins by extreme climate events. In Peru, the Pacific coastal basin and steep regions is particularly vulnerable to these events, which have caused significant damage and loss of life in recent years. This study aims to establish hourly rainfall thresholds for the initiation of mudflows events in Punta Hermosa, a region prone to these hazards. Acknowledging the shortcomings due to lack of observed precipitation data, this study utilizes gridded rainfall data to simulate mudflows events at an hourly scale. This methodology enables a more thorough investigation of rainfall patterns and their relationship with the occurrence of mudflows. Results indicates that the total rainfall during an event significantly influences the initiation of mudflows, with thresholds exceeding 10 mm consistently triggering these events. Furthermore, rainfall events lasting at least 5 h with an intensity of 1.13 mm/h or greater pose a substantial risk. The study emphasizes the significance of rainfall intensity, demonstrating that intensities surpassing 1.25 mm/h consistently result in mudflows. These findings offer valuable insights for developing reliable early warning systems and implementing effective mitigation strategies to safeguard vulnerable communities and infrastructure in Punta Hermosa and the applicability of this methodology for any other location in the Peruvian coast.